Pengaruh Disiplin Dan Kepuasan Kerja Terhadap Kinerja Karyawan PT. PLN - Yudhistira, Alfian; Ipijei, Irene (EKONOMI & SOSIAL, 2023)
This research aims to determine the influence of work discipline and job satisfaction on employee performance at PT. PLN Tarakan Distribusi Merauke. The population and sample used in this study consisted of 40 respondents. The research method used is quantitative research. Data sources include primary and secondary data collected through observation, interviews, questionnaires, documentation, and literature studies. The sample determination technique used in this study is total sampling, where the sample size equals the population size. Measurement in this research uses a Likert scale,a nd the data is analyzed using multiple linear regression with SPSS Version 25. The results of this study indicate that work discipline partially has a significant influence on employee performance at PT. PLN Tarakan Distribusi Merauke, as evidenced by the calculated t-value of 6.556 > t-table = 1.687. Similarly, job satisfaction partially has a significant influence on employee performance, with a calculated t-value of 3.188 > t-table = 1.687. Work discipline and job satisfaction simultaneously have a positive and significant influence on employee performance at PT. PLN Tarakan Distribusi Merauke, as shown by the results where F-table 3.25 < F-value 39.090 and sig is 0.000 < 0.05.